2016
DOI: 10.1515/jomb-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spectrophotometric and Fluorimetric Methods in Evaluation of Biotinidase Deficiency

Abstract: SummaryBackgroundBiotin, a water-soluble vitamin, is used as a co-factor by enzymes involved in carboxylation reactions. Biotinidase (BTD) catalyzes the recycling of biotin from endogenous and dietary sources. Biotinidase deficiency (BD) is an autosomal recessively inherited disorder of biotin recycling that is associated with neurologic and cutaneous consequences when untreated. The aim of the study was to compare the results of spectrophotometric and fluorimetric methods, as well as to evaluate the advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…62 A published comparison suggests that the fluorescence method using biotinyl-6-aminoquinoline as the substrate was slightly more specific and sensitive than the colorimetric assay. 63 Further studies are warranted to compare the various methods used for newborn screening.…”
Section: Newborn Screening For Biotinidase Deficiencymentioning
confidence: 99%
“…62 A published comparison suggests that the fluorescence method using biotinyl-6-aminoquinoline as the substrate was slightly more specific and sensitive than the colorimetric assay. 63 Further studies are warranted to compare the various methods used for newborn screening.…”
Section: Newborn Screening For Biotinidase Deficiencymentioning
confidence: 99%
“…Swiss NBS introduced BTD deficiency screening in 1987. The BTD enzyme activity in dried blood spots (DBS) was determined semi‐quantitatively using different colorimetric or fluorometric assays 14,15 . Acylcarnitines are not considered for the NBS of BTD deficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The BTD enzyme activity in dried blood spots (DBS) was determined semi-quantitatively using different colorimetric or fluorometric assays. 14,15 Acylcarnitines are not considered for the NBS of BTD deficiency. During the course of the presented study, the kits from PerkinElmer Inc. and Labsystems Diagnostics Oy have been used, which are utilizing as artificial BTD substrates europium-labeled biotin (GSP Neonatal biotinidase Kit, PerkinElmer) and biotinyl-6-aminoquinoline (Neonatal biotinidase kit, Labsystems Diagnostics Oy), respectively.…”
Section: Btd Enzyme Activity In Dried Blood Spotmentioning
confidence: 99%
“…Recently, a study indicated that the fluorimetric assay was slightly more sensitive to the colorimetric assay in identifying the deficiency [71]. However, the disparity would likely be in identifying partially deficient versus those with normal activity.…”
Section: What Questions About Biotinidase Deficiency and Its Newborn mentioning
confidence: 99%